Stress response and microstructural evolution of nickel-based superalloys during low cycle fatigue: Physics-based modelling of cyclic hardening and softening. (May 2020) - León-Cázares, F.D.; Monni, F.; Jackson, T.; Galindo-Nava, E.I.; Rae, C.M.F.
Abstract: Low cycle fatigue is one of the main life limiting factors in gas turbine discs. The plastic deformation behaviour that leads to crack initiation is not fully understood, and phenomenological descriptions fail to explain the stress response typical of nickel-based superalloys, which consists of cyclic hardening followed by cyclic softening. In this study, samples of nickel-based superalloy 718Plus with different ageing heat treatments are fatigued for 500 cycles at room temperature, their microstructures characterised and their slip localisation behaviour quantified via electron channelling contrast imaging (ECCI). A physics-based mesoscopic model is developed to investigate the effects of ageing and loading conditions on cyclic deformation behaviour. The formation of slip bands and evolution of the local dislocation density are used to describe cyclic hardening, while continued precipitate shearing from the accumulation of slip irreversibilities is modelled as the source of cyclic softening. Both mechanisms are then coupled via a parameter for the volume fraction of slip bands. The model successfully reproduces the trends observed for the different conditions, with overaged samples eventually surpassing the cyclic stress of the peak-aged specimens due to a slower softening rate. Curves from the literature for superalloy Nimonic PE16 are also reproduced for different ageing conditions and strain amplitudes. Further electron microscopy near surface cracks reveals the presence of precipitate-free deformation bands only in the underaged condition, which is explained in terms of a saturation point for the shearing process. Graphical abstract: Highlights: Slip localisation is promoted by the presence of coherent precipitates. Fast-Fourier-Transform processing allows estimating the slip band volume fraction. Cyclic hardening modelled from the heterogenisation of the dislocation structure. Cyclic softening modelled as a loss in strengthening due to precipitate shearing. Dissolution only of underaged precipitates near cracks due to extensive shearing.